The Selection of Outstanding Teachers to the Determination of Ranking on Professional and Intellectual Managerial Performances - Rismita, Rismita; Khuluqo, Ihsana El; Istaryatiningtias, Istaryatiningtias; Hendra, Akbar Nadjar (AT-TA'LIM, 2020)
The study aims to analyze the selection of outstanding teachers to the determination ranking on professional and intellectual managerial performances. A qualitative research was used where 91 teachers were selected based on the level of education from kindergarten to secondary school and vocational education. Â The results showed there are three data categories of professional and managerial performances of teachers, namely, high, medium and low. The three categories of data describe the various factors that affect the ability of the management professional and intellectual teachers among the demands of interpersonal of the profession, carrying out the task of teaching a high quality produces professional development, encouragement and motivation from leaders in the school, and a special confidence in the development of professional, as well as using the four dimensions (the assessment of emotion-self, appraisal of emotions of others, use of emotion, and emotion regulation) in improving the performance of teachers and the determination of the personal goals of the teacher in the academic achievement.